The Influence of Massage on Sleep Quality in Children's Pre-School - Hindyah Ike Suhariati; Endang Yuswatiningsih (Babali Nursing Research, 2020)
Introduction: Sleep disturbance is one of the problems that is often encountered in preschool children. About 44,2% of preschoolers experience sleep disorders. Sleep disorders can affect children's behavior and emotions, cause drowsiness during the day, reduce children's attention at school, get tired easily, reduce physical activity, reduce memory, children become fussy and temper tantrums. The purpose of this study is to analyze the effect of giving massage to sleep quality in preschool children in a Kindergarten in Lawang Hospital. Methods: The design in this study is the Pre-Experiment (Pre and Post-test design). The Affordable population is all preschool age children in a Kindergarten in Lawang who have 45 sleep disorders, the sample in this study amounted to 35 children. The sampling technique used was Simple Random Sampling. Analysis of paired data (pre and post-test) on sleep quality variables used the Wilcoxon test. If the statistical test results obtained p <0.05, then H1 is accepted, it means the research hypothesis is accepted. Results: The results showed the quality of sleep before giving massage mostly poor, the quality of sleep after giving massage is mostly good, there is an effect of giving massage to the quality of sleep in preschool children in a Kindergarten in Lawang. Conclusion: The study concludes that there is an effect of giving massage to the quality of timber in preschool children in a Kindergarten in Lawang.